2016
DOI: 10.3390/molecules21060782
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution α-Glucosidase Inhibition Profiling Combined with HPLC-HRMS-SPE-NMR for Identification of Antidiabetic Compounds in Eremanthus crotonoides (Asteraceae)

Abstract: α-Glucosidase inhibitors decrease the cleavage-and absorption rate of monosaccharides from complex dietary carbohydrates, and represent therefore an important class of drugs for management of type 2 diabetes. In this study, a defatted ethyl acetate extract of Eremanthus crotonoides leaves with an inhibitory concentration (IC 50 ) of 34.5 µg/mL towards α-glucosidase was investigated by high-resolution α-glucosidase inhibition profiling combined with HPLC-HRMS-SPE-NMR. This led to identification of six α-glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The material eluted as peak 1 was identified as protocatechuic acid (1) [16] (Figure 3) (data given in supplementary data Table S1) based on HR-MS analysis and comparison with literature data. The material eluted with the peaks 2, 3, 4, and 6 were identified as 4-hydroxybenzoic acid (2), [11] caffeic acid (3), [17] vanillic acid (4), [18] and ferulic acid (6) [19] based on the HR-MS and 1 H-NMR data (Table S1) in comparison with reference data from literature. Phenolic acids are widely spread throughout the plant kingdom and are well recognized as antioxidant constituents, which are protective against oxidative stress and display an important role in several alarm diseases such cancer, diabetes, and atherosclerosis.…”
Section: High-resolution Radical Scavenging Profile and Identificatiomentioning
confidence: 99%
See 1 more Smart Citation
“…The material eluted as peak 1 was identified as protocatechuic acid (1) [16] (Figure 3) (data given in supplementary data Table S1) based on HR-MS analysis and comparison with literature data. The material eluted with the peaks 2, 3, 4, and 6 were identified as 4-hydroxybenzoic acid (2), [11] caffeic acid (3), [17] vanillic acid (4), [18] and ferulic acid (6) [19] based on the HR-MS and 1 H-NMR data (Table S1) in comparison with reference data from literature. Phenolic acids are widely spread throughout the plant kingdom and are well recognized as antioxidant constituents, which are protective against oxidative stress and display an important role in several alarm diseases such cancer, diabetes, and atherosclerosis.…”
Section: High-resolution Radical Scavenging Profile and Identificatiomentioning
confidence: 99%
“…The material eluted with peaks 5 and 7 were elucidated as p-coumaric acid (5) [17] and 3,4-dimethoxy Figure 1. Schematic representation of high-resolution radical scavenging profiling combined with HPLC-HR-MS-SPE-NMR analysis of Athenaea martiana ethyl acetate extract.…”
Section: Identification Of Additional Secondary Metabolitesmentioning
confidence: 99%
“…Diabetes mellitus, one of the most serious and chronic metabolic diseases, has become a global health issue . In a clinical setting, α‐glucosidase inhibitors can delay the absorption of dietary carbohydrates to suppress postprandial blood glucose and insulin levels, and they have been widely used in the treatment of patients with type II diabetes . Synthetic α‐glucosidase inhibitors, such as acarbose and voglibose, displayed superior effects on reducing postprandial blood glucose .…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that the integrated ultrafiltration liquid chromatography with mass spectrometry method was an effective and powerful tool for the discovery of active ingredients in Shenqi Jiangtang Granule. K E Y W O R D S alpha-glucosidase inhibitors, diabetes mellitus, liquid chromatography-mass spectrometry, traditional Chinese medicine, ultrafiltration Abbreviations: CHM, Chinese herbal medicine; PNPG, p-nitrophenyl-α-D-galactopyranoside; SJG, Shenqi Jiangtang Granule; t R , retention time Conflict of interest: The authors declare no potential conflict of interest.blood glucose and insulin levels, and they have been widely used in the treatment of patients with type II diabetes [2,3]. Synthetic α-glucosidase inhibitors, such as acarbose and voglibose, displayed superior effects on reducing postprandial blood glucose [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation